Conjugated Polymers: Reversible Electronic Solid–Gel Switching of a Conjugated Polymer (Adv. Sci. 2/2020) - Gladisch, Johannes (Adv Sci (Weinh), 2020)
In article number https://doi.org/10.1002/advs.201901144, Eleni Stavrinidou, Magnus Berggren, and co‐workers present a conjugated polymer that exhibits unprecedented volume change when electrochemically addressed. The thiophene‐based polymer expands between 1000% and 10 000% irreversibly and 300% reversibly when oxidized. Molecular Dynamics reveal that the polymer transforms between a solid state to gelled state upon redox switching. [Image: see text]